Selective crystallization of four bis(phthalocyaninato)lanthanoid(iii) polymorphs. Issue 40 (24th September 2021) - Dailey, Maegan; Besson, Claire
Abstract : Four polymorphs of the bis-phthalocyanine lanthanoid(iii ) double-decker complexes are crystallized by solution evaporation methods, and their structures determined by single-crystal X-ray crystallography. Abstract : Bis(phthalocyaninato)lanthanoid(iii ) (LnPc2 ) complexes have attracted significant attention for their exceptional optical, electronic and magnetic properties. Crystallization of these compounds usually requires cumbersome methods such as sublimation and electrocrystallization, which is a significant limitation to both structural determinations and the preparation of high purity materials at scale. We report here the selective crystallization of four polymorphs of LnPc2 obtained exclusively by the slow evaporation of saturated solutions. The obtained phase depends on the initial oxidation state of the LnPc2 molecule and the choice of solvent. Single-crystal X-ray diffraction studies were used to determine 14 new structures including Ln = La, Pr, Nd, Sm, Gd, Tb, Dy, Er and Yb, as well as correct previous mis-identifications from the literature. We provide a detailed comparison of molecular structure and crystal packing in all LnPc2 polymorphs. The primary feature in all phases is columnar stacking based on parallel π–π interactions, with a variety of slip angles within those stacks as well as secondary interactions between them. Chemical redox and acid–base titrations, performed on re-dissolved crystals demonstrate that LnPc2 + and LnPc2 − are easily obtained through weak oxidizing and reducing agents, respectively. Additionally, we show that the protonated form of the NdPc2 − complex has a nearly identical UV-vis spectrum to that of neutral NdPc2, explaining some of the confusion over chemical composition in previously published literature.